THE IMPACT OF MOTIVATION ON ENGLISH LANGUAGE LEARNING - Alimova Khilola Rustamovna (Web of Journals Publishing, 2025)
This article discusses the development of effective teaching materials in English. Motivation plays a primary role in learning foreign languages. The search for optimal means of increasing it is an objective need in the field of education. Taking into account the data of pragma linguistics and the changed status of a foreign language as the main means of intercultural communication, modern methodology emphasizes the need to strengthen motivational aspects in learning a language.
Keywords: Motivation, types of motivation, foreign language, English, communicative competence, teaching methods, efficiency.